Study of effect of various temperatures on the abundance of ammonia oxidizing archaea and bacteria - KHANGEMBAM, CHERITA DEVI; SINGH, SAMAR PAL; CHAKRABARTI, RINA; SHARMA, JAIGOPAL (The Indian Journal of Animal Sciences, 2023)
Temperature plays significant role in the oxidation of ammonia in filtration units of recirculating aquaculture system. The impact of temperature on the abundance of ammonia oxidizing archaea and bacteria, and the expression of ammonia oxidizing gene (amoA) at specific temperature was evaluated. The broken earthen pot pieces used as filter bed materials of recirculating system, showing the presence of microorganisms were introduced in glass containers (5 pieces/5l) filled with synthetic wastewater and exposed to four different temperatures of 10, 20, 30 and 40°C for 40 days. The ammonia oxidation rate was minimum at 10°C. In 20, 30 and 40°C treatments, 99% ammonia was reduced on day-18, 8 and 18, respectively compared to the initial day. Fresh ammonium chloride (2 mM) was added twice to maintain the ammonia concentration in all treatments, except 10°C one. Nitrite-N level was < 1 mg/l at 10°C. The level was highest on day-22 at 20° and 40°C and on day-12 at 30°C. The nitrification was 10 days delayed at 20°C and 40°C compared to 30°C treatment. Concentration of nitrate-N was lowest at 10°C. Highest concentration of nitrate-N was observed on day-40 at 20°C and 40°C and day-26 at 30°C. Highest copy number of bacterial amoA was recorded at 30°C (2.59×107) followed by 20°C (4.08×106), 40°C (1.45×106) and 10°C (5.664×103). Archaeal amoA was highest at 30°C (7.47×103) followed by 40°C (2.98×102) and 20°C (46.8) treatments. Hence it may be concluded that 30°C temperature was optimum for the efficient and faster oxidation of ammonia in the present recirculating system.